2000
DOI: 10.1523/jneurosci.20-17-06374.2000
|View full text |Cite
|
Sign up to set email alerts
|

KIF5C, a Novel Neuronal Kinesin Enriched in Motor Neurons

Abstract: Kinesin superfamily proteins (KIFs) are the molecular motors conveying cargos along microtubules. KIF5s, the heavy chains of conventional kinesin (KHC), are originally identified members of KIFs, and neuronal KIF5A and ubiquitous KIF5B have been identified so far. In the present work, we cloned a novel member of KIF5, KIF5C, and generated specific antibodies against three KIF5s to investigate their distribution and functions. KIF5A showed pan-neuronal distribution in the nervous system. KIF5B showed a glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
238
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(259 citation statements)
references
References 63 publications
16
238
1
2
Order By: Relevance
“…Whereas Kif5b is ubiquitously expressed, Kif5a and Kif5c are enriched in neurons. The three proteins are highly homologous and functionally redundant (Kanai et al, 2000). We investigated the properties of GFP-Kif5c in neuronal and non-neuronal cells, and confirmed that it moves at a speed similar in vivo to that measured for the same motor in vitro.…”
Section: Introductionsupporting
confidence: 54%
“…Whereas Kif5b is ubiquitously expressed, Kif5a and Kif5c are enriched in neurons. The three proteins are highly homologous and functionally redundant (Kanai et al, 2000). We investigated the properties of GFP-Kif5c in neuronal and non-neuronal cells, and confirmed that it moves at a speed similar in vivo to that measured for the same motor in vitro.…”
Section: Introductionsupporting
confidence: 54%
“…Previously, we have identified 25 KIFs in mice (11,(18)(19)(20)(21)(22). Most were found by using molecular biological approaches.…”
Section: Resultsmentioning
confidence: 99%
“…KHCs form a highly related family (KIF5A, KIF5B, and KIF5C). KIF5B is expressed ubiquitously in many tissues (42), whereas KIF5A and KIF5C are specific to nerve tissue (18,22). Kinesin initially was characterized as a motor transporting membranous organelles anterogradely toward the plus end of microtubules and forming a crossbridge between membranous organelle and microtubules in nerve axons (32,39,40,43,44).…”
Section: Resultsmentioning
confidence: 99%
“…To study the roles of the three kinesins, including KLP6, in transport of mitochondria in neuronal cells, we used the motor domainless GFP fusion proteins, rather than gene silencing, because of both the redundant expression of the KIF5A, -B and -C genes and the alternative splicing of the KIF1B gene in neuronal cells (Aizawa et al, 1992;Tanaka et al, 1998;Kanai et al, 2000;Zhao et al, 2001). After 24 hours incubation with low serum medium containing retinoic acid, almost all axon-like neurites of the control cells contained many clusters of mitochondria (Fig.…”
Section: Three Kinesins Participate In Mitochondrial Movementsmentioning
confidence: 99%
“…KHC/KIF5 belongs to the kinesin-1 family and is a conventional kinesin that has been conserved evolutionarily. In mice, two brain-specific isoforms (KIF5A and KIF5C) have been identified in addition to a ubiquitous isoform (KIF5B) (Aizawa et al, 1992;Kanai et al, 2000). In mouse disruption of the gene encoding KIF5B is embryonic lethal, and the null mutant cells exhibit mitochondrial clustering at the perinuclear region (Tanaka et al, 1998).…”
Section: Introductionmentioning
confidence: 99%